Pengaruh Media Tiruan Gigi Anak Terhadap Hasil Belajar Pengurangan Bilangan 1-10 pada Siswa Kelas I Sekolah Dasar: Penelitian - Kurnia Shinta Latusindah; Meirza Nanda Faradita; Deni Adi Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the effect of Children's Tooth Imitation Media on the learning outcomes of subtraction of numbers 1-10 in first grade students at Sugihwaras Public Elementary School in Sidoarjo. The study used a quasi-experimental approach with a nonequivalent control group design. Data were collected through a multiple-choice learning outcome test that had been tested for validity and reliability. Data analysis used an Independent Sample t-test after first conducting prerequisite analysis tests, including the Kolmogorov-Smirnov normality test (p = 0.401 for the experiment and p = 0.605 for the control) and Levene's Test of homogeneity (p = 0.149). The results showed a significant difference between the experimental and control groups (t = 4.12; p = 0.000). The Effect size obtained was in the large category (Cohen's d = 1.12). Thus, it can be concluded that the Children's Tooth Imitation Media has a significant and substantive effect on the learning outcomes of 1-10 number reduction in first-grade elementary school students. This media is effective as a concrete and contextual learning aid in mathematics in accordance with the cognitive development characteristics of lower grade students.